Microstructural design opportunities and phase stability in the spray-formed AlCoCr0.75Cu0.5FeNi high entropy alloy - Vikas Shivam; Shubhada Kar; Gopi K. Mandal; N.K. Mukhopadhyay; V.C. Srivastava (Journal of Alloys and Metallurgical Systems)
Designing a microstructure with controlled morphology is one of the determining factors for the optimum performance of a material. High entropy alloys (HEAs) have gained significant attention due to their enhanced mechanical and functional properties compared to conventional alloys, particularly based on opportunities for microstructural design. In this fast-developing field, varied thermal treatments can be applied to engineer a material as per the requirements. In the present work, we have studied the effect of thermal treatment on the microstructural modifications in the spray-formed AlCoCr0.75Cu0.5FeNi HEA. The alloy was characterized by using a light microscope, scanning electron microscope equipped with EDS detector and electron probe micro analyzer (EPMA). The elemental distribution and microstructural evolution of the alloy were studied by giving the heat treatments at different time-temperature spaces. The evolution of phases and their composition were correlated with the CALPHAD predicted property diagram and phase composition. It is observed that at a higher temperature of 1300°C, the alloy shows the simple solid solution phases to be more stable due to the high entropy effect, which brings down the Gibbs free energy of the system. The formation of the disordered BCC, FCC and their derivatives along with the sigma phase were observed in the temperature range of 600–1000°C. This work also draws attention to why understanding the microstructural evolution and solidification behaviour is important in designing the HEAs to meet the industrial promises and in this context, the role of entropy, enthalpy and slow diffusion kinetics are discussed.